The Role of Environmental-Friendly Factors and Islamic Religiosity in Achieving Sustainable Consumption - Febrina Mahliza; Prita Prasetya; Riska Rosdiana; Putri Dwi Wahyuni (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: The circular economy aims to establish a sustainable system by maximizing and optimizing resources and capabilities, enabling businesses to provide greater value to consumers. Consumers’ perceptions of environmental values, along with their environmental concerns and knowledge, play a crucial role in encouraging efficient and sustainable consumption. Additionally, individuals with strong religious beliefs often exhibit pro-environmental attitudes, which may influence their intentions and behaviors in purchasing environmentally friendly products. Purpose: This study examines the role of eco-friendly factors and Islamic religiosity in shaping sustainable consumption behavior among Muslim women in Indonesia who purchase eco-friendly cosmetic products. Methods: This study employed a conclusive, descriptive, and cross-sectional research design. A total of 218 respondents were selected through purposive sampling. Data were collected through questionnaire distribution and analyzed using Partial Least Squares (PLS) structural equation modeling. Findings: The results indicate that eco-friendly factors—including environmental concern, environmental awareness, environmental knowledge, and environmental values—positively and significantly influence sustainable consumption. However, contrary to expectations, religiosity does not significantly impact sustainable consumption and does not moderate the relationship between sustainable consumption and behavioral intention. Additionally, sustainable consumption positively influences behavioral intention. Conclusion: These results highlight the crucial of environmental awareness and values in fostering sustainable consumption behavior. However, religiosity alone may not be a determining factor in consumers' eco-friendly purchasing decisions. Research implication: This study provides valuable insights for policymakers, businesses, and marketers to develop more effective sustainability campaigns and interventions by focusing on enhancing environmental awareness and values rather than relying solely on religious motivation to promote sustainable consumption.